Exploring the Potential of a Multi-Level Approach to Advance the Development of the Medical Tourism Industry in Indonesia - Supriadi; Badra Al Aufa; Ari Nurfikri; Ibrahim Isa Koire (SAGE Publishing, 2024)
Nowadays, the global medical tourism market size has grown quite rapidly, with a projected increase of 21.1% between 2021 and 2028. This study aimed to explore barriers and potential strategies for the development of medical tourism in Indonesia. A qualitative case study design was employed, where 8 respondents were selected using an expert sampling method from various groups according to the helix framework, including academics, government, professional organizations, the private sector, and the media. Data was collected through document analysis and in-depth interviews, and was analyzed manually using an inductive thematic content analysis approach. Limitations to the development of Indonesian medical tourism are related to regulations concerning medical tourism, the number of health services, distribution, supporting resources, public trust, and competition. At the institutional level, the challenges comprise services and products, hospital facilities, supporting facilities, and marketing processes. Furthermore, at the micro level, the low competency of both health and non-health workers persist as an obstacle. The potential strategy at the macro level include the development of robust marketing and branding strategies, health infrastructure, and resources. At the institutional level, it was necessary to develop related products and services provided, improve quality, and focus on branding and marketing strategies. Additionally, improving human resource skills was needed at the micro level.